Using information technology advancements to adapt to global pandemics - Idemudia, Efosa C. (Efosa Carroll), 1970-; Iyamu, Tiko; Ndayizigamiye, Patrick, 1979-; Shaanika, Irja Naambo, 1989- (Engineering Science Reference, 2022)
"This book provides insights and understanding on how companies and organizations are using advances in IT to adapt to global pandemics such as COVID-19, especially harnessing the power of various digital channels such as big data analytics and artificial intelligence to better serve their customers and business partners"--